The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1183/09031936.02.00288402
|View full text |Cite
|
Sign up to set email alerts
|

Spiral computed tomography of pulmonary embolism

Abstract: Spiral computed tomography of pulmonary embolism. C.J. Herold. #ERS Journals Ltd 2002. ABSTRACT: Within the last several years, spiral computed tomography angiography (SCTA) of the pulmonary arteries has emerged as a noninvasive angiographic modality for the evaluation of patients with suspected pulmonary embolism (PE). SCTA is based on continuous computed tomography (CT) data acquisition during patient transport through the rotating X-ray tube and detector system, where scanning is performed in the time perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 40 publications
(55 reference statements)
1
5
0
1
Order By: Relevance
“…As well as modulating microvascular tone in skin, NO has been implicated in the modulation of vascular permeability. Again, conflicting results exist on the role of NO in mediation of SP-induced protein extravasation [13, 14, 38, 52, 53, 54, 55]. In our study, a significant reduction of SP-induced protein extravasation was observed.…”
Section: Discussionsupporting
confidence: 63%
“…As well as modulating microvascular tone in skin, NO has been implicated in the modulation of vascular permeability. Again, conflicting results exist on the role of NO in mediation of SP-induced protein extravasation [13, 14, 38, 52, 53, 54, 55]. In our study, a significant reduction of SP-induced protein extravasation was observed.…”
Section: Discussionsupporting
confidence: 63%
“…The proportion of spiral CT examinations that give no result because of technical failure, or give an indeterminate result, is variously reported as 2-10% [49,68,101]. Errors can be caused by cardiac [102] or respiratory [49,103] artifacts, too little contrast medium [70,102] or anatomical factors such as hilar nodes [31] or peribronchovascular infi ltration [49,103]. First results from the early 1990s [104,105], admittedly only with acute central PE, indicated a sensitivity of nearly 100% and a specifi city of 96%.…”
Section: Spiral Ct In Comparison With Lpsmentioning
confidence: 99%
“…Leg US may be used in patients with subsegmental PE without central pulmonary artery involvement or in those with a negative spiral CT with leg symptoms, to investigate the presence of a lower limb DVT. It is important to diagnose or exclude presence of DVT in these patients as coexisting thrombus in leg veins can re‐embolize into the lungs 74 …”
Section: Other Imaging Investigationsmentioning
confidence: 99%
“…It is important to diagnose or exclude presence of DVT in these patients as coexisting thrombus in leg veins can re-embolize into the lungs. 74…”
Section: Leg Usmentioning
confidence: 99%